PENGARUH FINANCIAL LITERACY DAN FINANCIAL ATTITUDE TERHADAP PERILAKU KONSUMTIF MAHASISWA (STUDI KASUS PADA MAHASISWA FEB UNIVERSITAS PATTIMURA) - Kiat, Syifa Afrillia; Soepriadi, Dewi Nidia (Jurnal Akuntansi, 2025)
This study aims to determine the effect of Financial Literacy and Financial Attitude on Consumptive Behavior. This study used quantitative research methods by distributing questionnaires. The sampling technique in this study used a saturated sample technique. The population and sample were all students of the Faculty of Economics and Business, Department of Accounting, Class of 2020, totaling 150 respondents. The results of this study are, Financial Literacy has no significant effect on consumptive behavior while Financial Attitude has a negative and significant effect on consumptive behavior.